Patient characteristics associated with conversion from negative to positive severe acute respiratory syndrome coronavirus‐2 polymerase chain reaction test results: Implications for clinical false‐negativity from a single‐center: A case‐control study. Issue 10 (24th June 2022) - Atluri, Vidya L.; Stalter, Randy M.; McGuffin, Sarah A.; Johnson, Luke; Healy, Bailey; Benesch, Hailey A.; Lan, Kristine; Marsland, Paula; Pottinger, Paul; Patel, Rena C.
Abstract: Background: Accurate diagnosis of coronavirus disease 2019 is essential to limiting transmission within healthcare settings. The aim of this study was to identify patient demographic and clinical characteristics that could impact the clinical sensitivity of the nasopharyngeal severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV2) reverse transcription polymerase chain reaction (RT‐PCR) test. Methods: We conducted a retrospective, matched case‐control study of patients who underwent repeated nasopharyngeal SARS‐CoV2 RT‐PCR testing at a tertiary care academic medical center between March 1 and July 23, 2020. The primary endpoint was conversion from negative to positive PCR status within 14 days. We conducted conditional logistic regression modeling to assess the associations between demographic and clinical features and conversion to test positivity. Results: Of 51, 116 patients with conclusive SARS‐CoV2 nasopharyngeal RT‐PCR results, 97 patients converted from negative to positive within 14 days. We matched those patients 1:2 to 194 controls by initial test date. In multivariate analysis, clinical suspicion for a respiratory infection (adjusted odds ratio [aOR] 20.9, 95% confidence interval [CI]: 3.1–141.2) and lack of pulmonary imaging (aOR 4.7, 95% CI: 1.03–21.8) were associated with conversion, while a lower burden of comorbidities trended toward an increased odds of conversion (aOR 2.2, 95% CI: 0.9–5.3). Conclusions: Symptoms consistent with a respiratory infection, especially in relatively healthy individuals, should raise concerns about a clinical false‐negative result. We have identified several characteristics that should be considered when creating institutional infection prevention guidelines in the absence of more definitive data and should be included in future studies.